p0 and Drell-Söding contributions to central exclusive production of π+π- pairs in proton-proton collisions at high energies - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We present a study of the central exclusive π+π− production via the photoproduction mechanism in nucleon-nucleon collisions. The photon-pomeron/reggeon and pomeron/reggeon-photon exchanges both for the ρ(770) resonance, the Drell-Söding, and for the ρ(1450) contributions are considered. The amplitudes for the processes are formulated in terms of vertices respecting the standard crossing and charge-conjugation relations of quantum field theory. The coupling parameters of tensor pomeron and reggeon exchanges are fixed based on the HERA experimental data for the γp→ρ0p reaction. We present first predictions of this mechanism for the pp→ppπ+π− reaction being studied at COMPASS, RHIC, Tevatron, and LHC. We show the influence of the experimental cuts on the integrated cross section and on various differential distributions for outgoing particles. Distributions in rapidities and transverse momenta of outgoing protons and pions as well as correlations in the azimuthal angle between them are presented. We compare the photoproduction contribution to π+π− distributions with double pomeron/reggeon two-pion continuum including the absorption effects. We discuss whether the high-energy central production of isovector ρ resonances could be selected experimentally.